A Descriptive Study of Benign Vocal Cord Lesions with Speech Prameters Operated with Microlaryngoscopy (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: benign vocal cord lesion; grbas score; maximum phonation time; speech therapy